Strengthening Family Economy Through Sharia Financial Literacy Among Housewives in the Neighborhood of Rizki Bakti Foundation in Pekanbaru - Wali Saputra (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The primary objective of this community service initiative is to enhance Sharia financial literacy among housewives residing in the vicinity of Yayasan Rizki Bakti Negeri Pekanbaru, thereby facilitating the empowerment of the family economy grounded in Islamic principles. The principal challenges recognized included the inadequate comprehension within the community, particularly among mothers, regarding the management of household finances in accordance with Sharia, which encompasses insufficient practices in budget recording, the absence of long-term financial planning, and a lack of awareness pertaining to the halal and haram dichotomy in the utilization of financial products. The methodological framework of this initiative comprises four distinct phases: preparation, implementation, evaluation, and reporting, along with a sustainability strategy. The activities are executed through a participatory educational methodology, incorporating training sessions, simulations of household budget development, group discussions, and evaluative assessments conducted prior to and following the training. The outcomes of the initiative indicated a substantial enhancement in participants’ comprehension and attitudes towards Sharia-compliant financial management. This improvement is substantiated by elevated post-test scores, notable shifts in financial behaviors, and the emergence of participants’ initiatives aimed at establishing Sharia finance learning communities within their localities. This initiative has yielded tangible positive repercussions on the capacity of housewives to make informed and Islamic financial decisions. Furthermore, the program has garnered support from the foundation to ensure its sustainability. Consequently, Sharia financial literacy has been validated as a pivotal instrument in fostering family economic autonomy and reinforcing social resilience anchored in Islamic values.